Psycho-social problems identified by adult bone marrow transplant survivors - Ries, Adrienne Sandra (Department of Social Development, 2017)
Bone marrow transplantation (BMT) offers many patients who are diagnosed with leukaemia, lymphoma, myeloma and aplastic anaemia the opportunity of increased survival. Chemotherapy is one of the most common forms of treatment for cancer patients en-route to BMT, which is often a concomitant stressor in the patient's life. Due to the side effects of chemotherapy, patients are often required to remain in a protective isolation unit for several weeks at a time. In most cases, BMT constitutes the final phase of the treatment process. This procedure is not without its risks and may create significant psychosocial stress for patients. Social work intervention in the Department of Haematology at Groote Schuur Hospital has focused primarily on newly diagnosed patients and those patients undergoing transplantation. However, with the increased success of BMT, it is important to address the needs of cancer survivors. An ongoing support group with BMT survivors, provided the opportunity for the researcher to conduct a qualitative exploratory study of how survivors conceptualise and describe their current lives. To this end, fifteen group sessions were tape recorded and the self-identified issues raised by the members were organised into themes. It was ascertained that adjustment post BMT was stressful for most of the survivors. In general, survivors experienced numerous losses in terms of intimate and social relationships, memory and sexual functioning. Anxiety was pervasive and was heightened by an underlying fear of relapse. However, survivors also acknowledged the positive benefits of having been diagnosed with cancer and undergoing a BMT, such as improved family relationships, renewed interest in religion and the changing of attitudes and values. Members utilised numerous coping skills including denial, avoidance, rationalisation, confrontation and problem solving in an attempt to master their situation. The group experience was viewed favourably by members who formed a strong bond as a result of their shared experiences. Some of the survivors were able to use the group to express fears that they felt uncomfortable to express elsewhere. BMT survivors enter a distinct phase of adjustment with the re-entry into their premorbid lifestyles. Preparation is essential if this phase is to mastered. Further research across race and cultural groupings is required in order to ensure that social work intervention is appropriate to all in South Africa.